Ecological Restoration and Sustainable Development: The Impact of Wakaf Forest Institutions on Socio-Economic Benefits - Candra , Hari; Amar , Syamsul; Marta , Joan (Journal of Ecohumanism, 2024)
Indonesia is enhancing forest landscapes, particularly in deforestation-affected areas, through waqf forests to achieve environmental sustainability and community welfare. This study examines the ecological restoration processes within waqf forests and offers policy recommendations. It investigates causal relationships affecting waqf forest populations in Cibunian and Cibeureum villages using an ex post facto design and quantitative methods. Focusing on Cibunian beneficiaries, who generally possess higher education levels, the study explores the link between education and improved forest management. Data were collected via structured questionnaires and analyzed using Structural Equation Modeling (SEM). Findings reveal that the Waqf Forest Institution significantly impacts the socio-economic benefits of the waqf forest, contributing 26.4% to these benefits. Additionally, the institution enhances the ecological restoration of the waqf forest by 13.9%. The path coefficient value indicates a positive influence on the sustainability of these socio-economic benefits. Hypothesis testing confirms a significant impact of the Waqf Forest Institution, validating the alternative hypothesis (Ha). The Waqf Forest Institution is a vital resource for the local community, offering sustainable forest management and generating income. Managed in accordance with Indonesian laws and Islamic Sharia regulations, the institution strategically selects sites to improve service access and enhance the forest's role in livelihoods. The study underscores the importance of higher education in improving forest management and suggests policy frameworks support educational initiatives alongside ecological projects. Implications advocate for community-based financial models and strategic partnerships to address environmental challenges and promote sustainable development.